Cultural influences on lean manufacturing and productivity: Evidence from Malaysia - Ghazali, Ihwan; Tanjung, Tia; Al Humdan, Eias; Wan Mahmood, Wan Hasrulnizzam; Herawan, Safarudin Gazali; Sari, Wangi Pandan (Elsevier B.V., 2025)
This study investigates the impact of cultural values on the efficacy of lean manufacturing strategies within an emerging economy. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to look at data from a survey of 259 respondents from Malaysian manufacturing companies. Most research focuses on lean techniques and processes, but this study brings attention to the often-ignored significance of national culture. Within Hofstede’s five dimensions, only uncertainty avoidance demonstrated a slightly significant positive correlation (p < 0.10) with lean implementation success, suggesting that organized, risk-averse environments may facilitate lean adoption. There were no significant effects from power distance, individualism, masculinity, or long-term orientation. Human resource practices were recognized as the most significant predictor of production, emphasizing the necessity of employee involvement and skill enhancement. The findings enhance lean theory by situating implementation within cultural frameworks and provide pragmatic assistance for managers and policymakers aiming to harmonize lean strategies with local cultural characteristics in emerging nations.